Case Report of Acute Traumatic Rotator Cuff Tear Treatment in Traditional Korean Medicine - Jeong-Hwan Lee; Min-Kyung Ko; Kwang-Shik Yoon; Chang-Woo Lee; Young-Il Kim; Jung-Ho Kim (Korean Pharmacopuncture Institute, 2011)
Objectives: There is no report on treatment of acute traumatic rotator cuff tear in Traditional Korean Medicine. We reported Traditional Korean Treatment for pain relief and better movement of acute traumatic rotator cuff tear. Methods: Shoulder MRI was used to confirm the diagnosis of tear of rotator cuff. The patient was treated with Traditional Korean Methods (Acupuncture, Herbal medicine, Pharmacopuncture) for 6 months. We evaluated the patient through VAS (Visual Analogue Scale), UCLA shoulder scale, ROM (Range of motion) and Shoulder MRI. Results: After 6 months of treatment, the patient's VAS was decreased whereas UCLA score and Shoulder ROM were increased. Rotator cuff tear was repaired on Shoulder MRI images. Conclusions: In acute traumatic rotator cuff tear, Korean Traditional Treatment is good method for pain relief and better movement.